Perancangan Interior Edy Pirih Boxing Camp di Surabaya - Adi Santosa, Brian Suryanata (Intra, 2015)
Sports boxing in Surabaya branch in reality do not have adequate space and facilities, ranging from the standard and inadequate led to the growth of boxing underdeveloped and young seedlings that have no boxing talent can develop their potential well. Through interior design that implements the concept of "Transformation of young spirit" is expected to evoke the spirit of his special community youth so interested to practice the sport of boxing and also in the presence of adequate facilities can spur so excited to practice in this boxing gym.The concept of "Transformation of young spirit" uses the style of urban design. The concept of "Transformation" itself was taken because he wanted to show the impression of the atmosphere of the room at Edy Pirih original boxing camp so at the lobby using bricks that are colored white paint coupled with wall hangings such as poster art and occurs the change from the original space into a lobby that is both modern in another room of her, while the "young spirit" is a form of style urban design application that is composed of gravity, murals, and poster art which refers to the young style.